Hypoxia-Inducible Factors (HIFs) and Phosphorylation: Impact on Stability, Localization, and Transactivity - Kietzmann, Thomas; Mennerich, Daniela; Dimova, Elitsa Y. (Frontiers in Cell and Developmental Biology, 2016)
The hypoxia-inducible factor alpha-subnits (HIFs) are key transcription factors in the mammalian response to oxygen deficiency. The HIF-alpha regulation in response to hypoxia occurs primarily on the level of protein stability due to posttranslational hydroxylation and proteasomal degradation. However, HIF alpha-subunits also respond to various growth factors, hormones, or cytokines under normoxia indicating involvement of different kinase pathways in their regulation. Because these proteins participate in angiogenesis, glycolysis, programmed cell death, cancer, and ischemia, HIFalpha regulating kinases are attractive therapeutic targets. Although numerous kinases were reported to regulate HIFalpha indirectly, direct phosphorylation of HIFalpha affects HIFalpha stability, nuclear localization, and transactivity. Herein, we review the role of phosphorylation-dependent HIFalpha regulation with emphasis on protein stability, subcellular localization and transactivation.